Mandibular condylar hyperplasia: diagnosis and management. Case report - Pinto,Isabel (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: Mandibular condylar hyperplasia is a disease where excessive growth of mandibular condyle, ramus and body elicits facial asymmetry. Its therapeutic management is not a consensus and, due to its complexity, is a challenge for maxillofacial surgeons and orthodontists. This study aimed at discussing clinical, diagnostic and therapeutic aspects of the management of this disease, and at explaining the role of condylectomy. CASE REPORT: Female patient, 19 years old, Caucasian, looked for maxillofacial surgeon assistance due to facial asymmetry and pain on right temporomandibular joint. Patient had no medical, gestational or family history of facial deformity, or history of previous joint trauma or infection. This was a case of hemimandibular elongation treated with condylectomy. CONCLUSION: Condylectomy is a safe and effective procedure, without functional joint sequelae, which prevents dentalfacial deformity progression, minimizing its psychosocial impact and helping future treatment.